Wholeness, Hypocrisy, and Leadership - Christian Holmgaard (Scandinavian Journal for Leadership & Theology, 2023)
Theorists on Christian leadership on a broad scale embrace servant leadership theory (Åkerlund, 2015; Bredfeldt, 2006, pp. 88–89). There is, however, also an awareness of the deficiencies of the theory in light of Christian realism. This article looks at what may be called the dark side of leadership posed by the challenge of the problem of evil in theological anthropology. There are of course several dark sides of leadership and the one which is addressed here is the problem of hypocrisy in Christian leadership. Against this backdrop, Jesus’ criticism of the hypocrisy of some Jewish religious leaders may be helpful with Matthew 23 as the central text. In this chapter which Benedict Viviano has called the least loved chapter in the gospel of Matthew (Viviano, 1990, p. 3), Jesus provides a scathing attack on the contemporary Jewish religious leaders. The criticism of the leadership gives several negative principles for Christian leadership and the overall problem may be identified as hypocrisy. This article analyzes the problem of hypocrisy in leadership in Matthew’s gospel situated within the gospel itself and the overarching theological concern. Whereas hypocrisy is identified as Matthew’s moral nightmare, the moral dream may be called wholeness, providing the consistency between the inward nature of a person which the hypocrite lacks. A distinct Matthean response to the problem of hypocrisy in Christian leadership is formulated both by way of identifying hypocrisy and by describing the path towards wholeness through repentance and God-centered living which is laid out in Matthew’s gospel.